2015
DOI: 10.1213/ane.0000000000000931
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine as a Rapid Bolus for Treatment and Prophylactic Prevention of Emergence Agitation in Anesthetized Children

Abstract: Rapid IV bolus administration of DEX in children improved their recovery profile by reducing the incidence of EA. A statistically significant change in hemodynamics was observed, but no patients required any intervention for hemodynamic changes. Furthermore, DEX reduced the incidence of postoperative opioid administration, and a trend of fewer adverse events was observed in group DEX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 32 publications
1
56
1
Order By: Relevance
“…This paradoxical response to dexmedetomidine has been previously described [4] after a high-dose dexmedetomidine intravenous bolus, and it is believed to be due to activation of α 2B peripheral adrenergic receptors leading to vasoconstriction and increased systemic vascular resistance [11, 17]. Interestingly, this patient had received dexmedetomidine in a previous admission and experienced the expected decrease in BP and HR.…”
Section: Discussionsupporting
confidence: 53%
“…This paradoxical response to dexmedetomidine has been previously described [4] after a high-dose dexmedetomidine intravenous bolus, and it is believed to be due to activation of α 2B peripheral adrenergic receptors leading to vasoconstriction and increased systemic vascular resistance [11, 17]. Interestingly, this patient had received dexmedetomidine in a previous admission and experienced the expected decrease in BP and HR.…”
Section: Discussionsupporting
confidence: 53%
“…Dexmedetomidine is a highly selective α2‐adrenoceptor agonist with sedative, analgesic, and anxiolytic actions without respiratory depression, and it has been widely used in various clinical situations . Dexmedetomidine appears to be effective in a wide range of doses and is reported to have a short half‐life, about 1.8 hours .…”
Section: Discussionmentioning
confidence: 99%
“…Having an objective and validated scoring system to define EA is critical. Several scales have been used to assess EA; among them, the PAED scale by Sikich and Lerman and five scales by Cole et al have been validated and are used widely . In several studies, the two scoring systems showed similar results and were complementary in some parts .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations